Prediction of the compressive strength of one-part geopolymers - Abdollahnejad, Zahra (2015)
The discovery of one-part geopolymers is considered a key event on the evolution of geopolymer technology because emulates one of the most important properties of Portland cement, the just add water concept. This materials are not associated with the known problems of two part geopolymers, namely the use of caustic solutions that have poor workability and make the handling and application of geopolymers difficult and the fact that alkaline or soluble silicates are not consumed during geopolymerization leading to severe efflorescence phenomena. However, so far very few investigations were published on this field and some report low mechanical strength. This paper discloses results regarding the numerical modelling of one part-geopolymers compressive strength.